2015
DOI: 10.1037/cep0000049
|View full text |Cite
|
Sign up to set email alerts
|

Congruency effects on recognition memory: A context effect.

Abstract: Two recent studies have reported that incongruent selective attention items are better remembered than congruent items on a surprise recognition memory test (Krebs, Boehler, De Belder, & Egner, 2013;Rosner, D'Angelo, MacLellan, & Milliken, 2014). These findings suggest that an increased need for cognitive control may trigger encoding mechanisms at the time of study that result in better recognition of those items at test, a form of the desirable difficulty effect (Bjork, 1994). The experiments in the present p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A somewhat related literature has assessed incidental memory for the actual task stimuli in Stroop-type paradigms, with rather mixed results. Here, some studies have shown that participants can better remember incidentally encoded incongruent relative to congruent target stimuli, suggesting that conflict can enhance memory (Davis et al, 2019; Krebs et al, 2015; Ptok et al, 2019; Ptok et al, 2020; Rosner et al, 2015; Rosner & Milliken, 2015), while others have found null results or worse memory for incongruent targets (Jiménez et al, 2020; Ortiz-Tudela et al, 2017). Moreover, there is debate on whether putative memory enhancements may be driven by response conflict or semantic conflict (Muhmenthaler & Meier, 2019; Ptok et al, 2019; Ptok et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…A somewhat related literature has assessed incidental memory for the actual task stimuli in Stroop-type paradigms, with rather mixed results. Here, some studies have shown that participants can better remember incidentally encoded incongruent relative to congruent target stimuli, suggesting that conflict can enhance memory (Davis et al, 2019; Krebs et al, 2015; Ptok et al, 2019; Ptok et al, 2020; Rosner et al, 2015; Rosner & Milliken, 2015), while others have found null results or worse memory for incongruent targets (Jiménez et al, 2020; Ortiz-Tudela et al, 2017). Moreover, there is debate on whether putative memory enhancements may be driven by response conflict or semantic conflict (Muhmenthaler & Meier, 2019; Ptok et al, 2019; Ptok et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…However, recognition memory has also been shown to be improved for items previously presented with incongruent versus congruent distractors. Here, the increased need for cognitive control is thought to facilitate target encoding at the time of study improving later memory recognition (Krebs, Boehler, De Belder, & Egner, 2015; Rosner, D’Angelo, MacLellan, & Milliken, 2015; Rosner & Milliken, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Incongruent words subsequently showed better recognition memory. Follow-up studies showed that this recognition memory effect was not simply driven by the additional time on task for incongruent trials in the word naming phase (Rosner and Milliken, 2015), but appears to be a consequence of the increased selective attention demands for incongruent items.…”
Section: Introductionmentioning
confidence: 99%